2018
DOI: 10.1021/acsami.8b10009
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Deposition of Ultrathin Copolymer Films with Tunable Viscoelasticity for Application to Pressure-Sensitive Adhesives

Abstract: A new fabrication method for an ultrathin (500 nm thick) pressure-sensitive adhesive (PSA) was demonstrated by utilizing a series of in situ cross-linked viscoelastic copolymer films. Viscoelastic films composed of poly(2-hydroxyethyl acrylate- co-2-ethylhexyl acrylate) were synthesized successfully in a one-step manner by an initiated chemical vapor deposition (iCVD) process, where free-radical polymerization is triggered in the vapor phase either by heat or UV, or a combination of both. In particular, the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…For laminating substrates, parts, and encapsulation layers for flexible and stretchable devices, durability is enhanced by reducing the overall stacking thickness, including the need for thinner adhesive layers. High-shear strength iCVD pressure sensitive adhesives require only 500 nm of thickness 108 , a 200-fold reduction over conventional pressure sensitive adhesives. Controlling the degree of crosslinking in the iCVD copolymer led to the viscoelastic behavior required for interfacial bonding.…”
Section: Organic and Hybrid Devicesmentioning
confidence: 99%
“…For laminating substrates, parts, and encapsulation layers for flexible and stretchable devices, durability is enhanced by reducing the overall stacking thickness, including the need for thinner adhesive layers. High-shear strength iCVD pressure sensitive adhesives require only 500 nm of thickness 108 , a 200-fold reduction over conventional pressure sensitive adhesives. Controlling the degree of crosslinking in the iCVD copolymer led to the viscoelastic behavior required for interfacial bonding.…”
Section: Organic and Hybrid Devicesmentioning
confidence: 99%
“…The G′ and G″ were retained almost constant up to 200 °C, demonstrating no significant change in the elastic property nor thermal decomposition of pDVB. 37 Moreover, the loss factor (tan δ), defined by the ratio between G′ and G″ (G″/G′), was maintained less than one, while the G′− G″ crossover was not observed throughout the measured temperature range. All these analysis results clearly confirm that the pDVB preserved the intrinsic elastic property in a wide temperature range.…”
mentioning
confidence: 93%
“…Different balances between the liquid-like component and solid-like component can lead to different PSA performances [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that high performance PSA must have a proper combinational property of both liquid-like (viscous part) and solid-like (elastic part), and the liquid-like means a low modulus of elasticity and a high dissipation of viscosity, whereas the solid-like means a high modulus of elasticity and a low dissipation [ 8 , 10 ]. Different balances between the liquid-like component and solid-like component can lead to different PSA performances [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%